2010
DOI: 10.1016/s1734-1140(10)70264-4
|View full text |Cite
|
Sign up to set email alerts
|

Buspirone improves 6-hydroxydopamine-induced catalepsy through stimulation of nigral 5-HT1A receptors in rats

Abstract: Receptors for 5-HT(1A) are widely distributed throughout the basal ganglia, and their activation results in an inhibition of dopamine (DA) release. This study aimed to investigate the effect of buspirone, as a partial agonist of 5-HT(1A) receptors, on 6-hydroxydopamine (6-OHDA)-induced catalepsy in male Wistar rats. Catalepsy was induced by unilateral infusion of 6-OH-DA (6 microg/2 microl/rat) into the central region of the substantia nigra pars compacta (SNc) and assayed by the bar-test method 60, 120 and 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 29 publications
4
15
0
Order By: Relevance
“…This is in accordance with results of our previous studies concerning an anti-cataleptic effect for 5-HT 1A agonists in 6-OHDA (11) and haloperidole (12) induced PD.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is in accordance with results of our previous studies concerning an anti-cataleptic effect for 5-HT 1A agonists in 6-OHDA (11) and haloperidole (12) induced PD.…”
Section: Discussionsupporting
confidence: 93%
“…Stimulation of 5-HT 1A receptors in these regions leads to dopamine release (9) via inhibition of adenyl cyclase and opening of potassium channels (10). Recently it was shown that 5-HT 1A agonists exert anti-cataleptic effect in animal model of PD (11, 12) and also regulatory effect of 5-HT 1A receptors on L-DOPA derived dopamine levels has been reported (13). However there is no report about 5-HT 1A effects on anti-cataleptic effect of L-DOPA.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the wood block test, the standard bar test has also been routinely used for the measurement of cataleptic side effects of neuroleptic drugs (Nayebi et al, 2010). The apparatus consists of a bar placed horizontally several centimeters above the floor of a test box.…”
Section: Bar Testmentioning
confidence: 99%
“…The standard bar test has been routinely used for measurement of catalapetic side effects of neuroleptic drugs [20]. The bar test consists of a bar kept horizontally several centimetres above the floor of a test box.…”
Section: Bar Testmentioning
confidence: 99%